Factors Affecting Users' Purchase Intention and Attitudes towards Mobile Advertising - Clarita Nainggolan; Fatimah Azzahro; Putu Wuri Handayani (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
The growing number of mobile users encourages companies to take advantage of these opportunities to improve their marketing strategy. One of the marketing strategies that can be done through mobile devices is mobile advertising. However, the problem is that many users still consider mobile advertising as spam and many companies do not know how to start mobile advertising. While to start mobile advertising, must first understand the attitude of mobile users themselves. Therefore, this study aims to analyze the factors that can affecting Tokopedia application user's attitude to mobile advertising seen from affective and cognitive side. Additionally, this study aims to analyze the impact of mobile advertising on purchase intention of users to purchase products or services offered through mobile advertising. This research uses quantitative approach which is done by collecting respond from 565 Tokopedia application user's. The data is then analyzed using CB-SEM method using AMOS 21. Based on the results of analysis, the writers found that perceived ease of use, perceived usefulness, positive emotions, and negative emotions affect the user's attitude towards mobile advertising. Next, attitude also has an effect on user's purchase intention on advertised products or services.